IMPROVING THE METHODOLOGY FOR DEVELOPING INFORMATION AND COMMUNICATION COMPETENCIES OF FUTURE ENGINEERS IN A DIGITAL LEARNING ENVIRONMENT - Eshpulatova Husniya (Bright Mind Publishing, 2026)
The article examines the issues of improving the methodology for developing information and communicative competencies of future engineers in a digital educational environment. The main goal of the study is to identify the pedagogical capabilities of a modern digital educational environment in the process of engineering education and to develop methodological approaches aimed at the effective formation of information and communicative competencies. The article provides a scientific and theoretical analysis of the components of the digital educational environment, their role and significance in the educational process.